2014
DOI: 10.1002/ange.201309820
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Palladium‐Catalyzed Insertion of α‐Aryl‐α‐diazoacetates into the OH Bonds of Phenols

Abstract: A palladium-catalyzed asymmetric O À H insertion reaction was developed. Palladium complexes with chiral spiro bisoxazoline ligands promoted the insertion of a-aryl-adiazoacetates into the OÀH bond of phenols with high yield and excellent enantioselectivity under mild reaction conditions. This palladium-catalyzed asymmetric O À H insertion reaction provided an efficient and highly enantioselective method for the preparation of synthetically useful optically active a-aryl-aaryloxyacetates.Palladium is an indisp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Initially,wefocused our attention on the establishment of the optimal reaction conditions for the CÀHfunctionalization of 2a using 1a.T oo ur gratification, by employing L1 as aligand, the reaction proceeded smoothly under the catalysis of [Pd(PhCN) 2 Cl 2 ]inCH 2 Cl 2 ,thus giving the desired product with 97 % ee ( Table 1, entries [1][2][3][4][5][6][7][8]. Theevaluation of ligands showed that the previously reported L2 also promoted the reaction, but because of its small dihedral angel upon chelation, 86 % ee was obtained (entry 9).…”
mentioning
confidence: 99%
“…Initially,wefocused our attention on the establishment of the optimal reaction conditions for the CÀHfunctionalization of 2a using 1a.T oo ur gratification, by employing L1 as aligand, the reaction proceeded smoothly under the catalysis of [Pd(PhCN) 2 Cl 2 ]inCH 2 Cl 2 ,thus giving the desired product with 97 % ee ( Table 1, entries [1][2][3][4][5][6][7][8]. Theevaluation of ligands showed that the previously reported L2 also promoted the reaction, but because of its small dihedral angel upon chelation, 86 % ee was obtained (entry 9).…”
mentioning
confidence: 99%
“… 371 Zhou has applied the SpiroBOX ligands 1060 to asymmetric Cu-catalyzed α-diazo phosphonate carbenoid O–H insertions 372 and Pd-catalyzed carbenoid insertions into phenol O–H bonds. 373 …”
Section: Bis(oxazoline) Ligandsmentioning
confidence: 99%
“…The standard Wang conditions use both palladium and silver salts and both of these metal salts could potentially catalyze the decomposition of diazo compounds. [13] Scheme1.New synthetic route to TCE aryldiazoacetates.[b] Dr.E.A.V oight Research&Development, AbbVie 1N orth Waukegan Road, North Chicago, Illinois 60064( USA)[ + + ] These authors contributed equally to this work.Supporting information and the ORCID number(s) for the author(s) of this articlecan be foundu nder http://dx.…”
mentioning
confidence: 99%
“…The standard Wang conditions use both palladium and silver salts and both of these metal salts could potentially catalyze the decomposition of diazo compounds. [13] Scheme1.New synthetic route to TCE aryldiazoacetates.…”
mentioning
confidence: 99%
See 1 more Smart Citation